Drylands located in rangelands, with country boundaries - Getahun, Yasin; Flintan, Fiona E. (International Livestock Research Institute, 2018)
This map shows Drylands found in Rangelands (using global aridity classes) mapped against country boundaries providing approximate areas of Drylands found in rangelands per country. Aridity zones were derived from an Aridity Index (AI) which is calculated as the ratio of precipitation to potential evapotranspiration. Zones included in this dataset are: hyperarid, arid, semiarid, and dry subhumid. These are in accordance with the United Nations Convention to Combat Desertification (UNCCD) definition of Drylands and previously mapped by UNEP-WCMC 2007. Rangeland types and boundaries were previously mapped by University of Idaho and the Society for Rangeland Management (SRM). Country boundaries were taken from ESRI 2016.